Studi Potensi dan Perencanaan Pembangkit Listrik Tenaga Mikro Hidro Di Bendung Simbang Kecamatan Doro Kabupaten Pekalongan - M. Fanis Abdillah; Gunawan Gunawan; Agus Suprajitno (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2022)
The impact of greenhouse gas emissions is getting higher due to the use of fossil energy to drive power plants. Efforts to replace it is to develop renewable energy that is popular in Indonesia is micro hydro technology. This study aims to determine the potential of water energy and plant planning at Simbang Weir in Pekalongan. The method used combines water flow measurements with floating techniques and uses geographic information provided by Google Earth. The result of this research is that the water discharge is measured at 3.67 m3/s with a height of 11 meters. The turbine design uses crossflow with a potential power of 280.11 kW. The detailed engineering design is described in full in this study.